Co-doped hard carbon active material and preparation method and application thereof

Through the preparation method of co-doped hard carbon active materials, the doping of phosphorus oxides and nitrogen and sulfur atoms is solved, and the problems of low first-efficiency and low reversible capacity of hard carbon materials in sodium ion batteries are achieved, achieving a significant improvement in reversible capacity and first-efficiency.

CN119898744APending Publication Date: 2025-04-29SHENZHEN CITY THROUGH SCI & TECH OF NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311407234.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The lower first effect and low reversible capacity of hard carbon materials in sodium ion batteries limit their further applications.

Method used

By the preparation method of co-doped hard carbon active material, the crystal plane spacing of hard carbon is increased by using phosphorus oxide doping, and the morphology and coating structure of rGO are improved by doping nitrogen and sulfur atoms, thereby improving the reversible capacity and first effect of hard carbon materials.

Benefits of technology

It significantly improves the reversible capacity and first effect of hard carbon materials, maintains high Coulomb efficiency, and is suitable for sodium ion battery electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898744A_ABST
    Figure CN119898744A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a co-doped hard carbon active material and a preparation method and application thereof.The preparation method comprises the steps that S1, hard carbon particles and phosphate are jointly ball-milled to be uniform, and first powder is obtained; s2, in the protective atmosphere, heat preservation is conducted for 4-6 hours at the temperature of 1000-1500 DEG C, and second powder is obtained; s3, jointly adding the graphite powder and sodium nitrate into a concentrated sulfuric acid solution, stirring for 0.5-1 hour, keeping the temperature of the solution at 0-20 DEG C, continuously adding potassium permanganate powder, continuously stirring for 2 hours, then carrying out vacuum drying to obtain third powder, and annealing the third powder at 600-1200 DEG C for 12 hours to obtain fourth powder; s4, the second powder, the fourth powder, thiourea and urea are subjected to heat preservation for 1-2 hours at the temperature of 500-600 DEG C in the protective atmosphere in the continuous stirring state, then the temperature is increased to 750-950 DEG C, heat preservation is conducted for 1-2 hours, the materials are taken out and ground, and the co-doped hard carbon active material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and in particular to a co-doped hard carbon active material and a preparation method and application thereof. Background Art

[0002] In the related technologies, among the negative electrode materials for sodium-ion batteries, hard carbon negative electrode has the advantages of low energy storage voltage, high capacity, abundant sources, and simple preparation process. It is one of the negative electrode materials with the most application prospects. Hard carbon, by definition, refers to carbon that is difficult to graphitize. It is usually difficult to graphitize even at high temperatures above 2500°C. It has disordered graphite-like microcrystalline layers (the interlayer spacing is usually larger than that of graphite) and a large number of pore structures. Therefore, for sodium ions with larger ionic radius, hard carbon is more suitable as a negative electrode material than graphite. It can store more sodium ions, has a higher specific capacity, and the sodium ion deintercalation process is more stable. However, hard carbon materials have problems such as low initial efficiency and low reversible capacity, which hinder the further application of hard carbon materials. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a co-doped hard carbon active material and a preparation method and application thereof, which can improve the reversible capacity of the hard carbon material.

[0004] According to the preparation method of co-doped hard carbon active materials of the first aspect embodiment of the present application, S1: ball-mill hard carbon particles and phosphate together to obtain a first powder; S2: keep the first powder in a protective atmosphere at 1000°C to 1500°C for 4 to 6 hours to obtain a second powder; S3: add graphite powder and sodium nitrate into a concentrated sulfuric acid solution, and stir for 0.5 to 1 hour, maintain the solution temperature at 0°C to 20°C, continue to add potassium permanganate powder, and continue stirring for 2 hours, then vacuum dry to obtain a third powder, anneal the third powder at 600°C to 1200°C for 12 hours to obtain a fourth powder; S4: keep the second powder, the fourth powder, thiourea and urea at 500°C to 600°C in a protective atmosphere for 1 to 2 hours under continuous stirring, then increase the temperature to 750°C to 950°C and keep it for 1 to 2 hours, take out and grind to obtain a co-doped hard carbon active material.

[0005] The co-doped hard carbon active material according to the embodiment of the present application has at least the following beneficial effects: Because phosphorus oxide doping increases the larger interplanar spacing of hard carbon, the larger interplanar spacing promotes the intercalation of more sodium ions between the carbon layers inside the hard carbon, thereby increasing the platform capacity. At the same time, phosphorus oxide can introduce more defects in the local structure along the ab plane, further increasing the capacity of the platform and slope areas. Nitrogen and sulfur atoms are doped into rGO, which changes the morphology of rGO, increases the wrinkles into a rough tray-like flake morphology where particles aggregate, and makes the rGO doped with sulfur and nitrogen atoms coated on the surface of the hard carbon powder, which improves the reversible capacity and first efficiency of the hard carbon active material and maintains a high coulombic efficiency.

[0006] According to some embodiments of the present application, in S4, the second powder, the fourth powder, thiourea and urea are put into the barrel of a high-temperature coating machine, the agitator speed is set to 75 to 130 rpm, the heating temperature is increased to 500 to 600°C at a rate of 5°C / min, and the mixture is kept warm for 1 to 2 hours under a protective atmosphere. Subsequently, the heating temperature is set to increase to 750 to 950°C at a rate of 5°C / min, and the mixture is kept warm for 1 to 2 hours. The co-doped hard carbon active material is taken out and ground.

[0007] According to some embodiments of the present application, in S3, graphite powder and sodium nitrate are added together to a concentrated sulfuric acid solution and stirred for 0.5 hour to 1 hour, and potassium permanganate powder is continued to be added under ice bath conditions, the solution temperature is maintained at 0°C to 20°C, and stirring is continued for 2 hours, 30% hydrogen peroxide solution is slowly dripped into the solution, and then 10% dilute hydrochloric acid and deionized water are added to make the pH value of the solution 6-7, followed by vacuum drying to obtain a third powder, and the third powder is annealed at 600°C to 1200°C for 12 hours to obtain a fourth powder.

[0008] According to some embodiments of the present application, the phosphate is at least one of sodium hydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate or sodium ammonium hydrogen phosphate.

[0009] According to some embodiments of the present application, the mass ratio of graphite powder to sodium nitrate is 3:2.

[0010] According to some embodiments of the present application, the mass ratio of the second powder, the fourth powder, thiourea and urea is 30:5:1:1.

[0011] According to some embodiments of the present application, the hard carbon particles are obtained by sequentially washing, drying, crushing and sieving walnut shell hard carbon materials, and the hard carbon particles are 400 mesh to 600 mesh.

[0012] According to some embodiments of the present application, the protective atmosphere includes at least one component selected from nitrogen, helium, neon, argon or krypton.

[0013] According to some embodiments of the present application, a co-doped hard carbon active material prepared by the above-mentioned co-doped hard carbon active material preparation method is proposed.

[0014] According to some embodiments of the present application, a co-doped hard carbon active material prepared by the above-mentioned co-doped hard carbon active material preparation method is proposed as an application of a sodium ion battery electrode material.

[0015] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present application is further described below in conjunction with the accompanying drawings and embodiments, wherein: Figure 1 This is a schematic diagram of a process for preparing a co-doped hard carbon active material according to an embodiment of the present application; Figure 2 This is a schematic diagram of an emission scanning electron microscope (SEM) of a co-doped hard carbon active material according to an embodiment of the present application; Figure 3 A schematic diagram of the cycle performance and coulombic efficiency of a battery assembled with a co-doped hard carbon active material prepared in an embodiment of the present application; Figure 4 Schematic diagram of the charge and discharge curves of a battery assembled with co-doped hard carbon active materials prepared in an embodiment of the present application. Implementation

[0017] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0018] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0019] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0020] The following is a further description of the present invention, rather than a limitation of the present invention. Example

[0021] like Figure 1 As shown, a walnut shell hard carbon material is washed, dried, crushed, and sieved in sequence to obtain 400-mesh hard carbon particles, the hard carbon particles are added to a ball mill, and sodium hydrogen phosphate powder is added, and the mixed powder is obtained by ball milling. The ball milling can make the hard carbon particles and the sodium hydrogen phosphate powder mix evenly to obtain a mixed powder, i.e., the first powder, and the mixed powder is added to a graphite sagger, and the graphite sagger is transferred to a tubular furnace, and is kept at 1000°C for 6 hours under a nitrogen protective atmosphere. After cooling to room temperature with the furnace, the hard carbon powder is taken out, i.e., the second powder, and the sodium hydrogen phosphate is pyrolyzed into phosphorus oxides and doped into the hard carbon powder at the same time. The phosphorus oxide doping increases the (002) crystal plane spacing of the hard carbon from 3.79 Å to 3.86 Å. Å, the (002) peak moves from 23.6° to 23.0°, and the (002) peak moves from 1.78° to 1.76°. The larger (002) interplanar spacing can increase the capacity of hard carbon materials for sodium ion storage, thus significantly increasing the platform capacity. The larger interplanar spacing promotes the intercalation of more sodium ions between the carbon layers inside the hard carbon. At the same time, phosphorus oxide can introduce more defects in the local structure along the ab plane, thereby increasing the capacity of the platform and slope regions.

[0022] Take 3g of graphite powder and 2g of sodium nitrate, add them to concentrated sulfuric acid, put them in a magnetic stirrer and stir them continuously for 0.5 to 1h to obtain a mixed solution, take out the mixed solution for ice bath, and slowly add potassium permanganate powder to the mixed solution until the solution is dark brown, and control the temperature of the mixed solution below 20°C to prevent overheating and explosion. Continue stirring for 2h, keep the ice bath state during the period, and then add 100ml of deionized water to the solution to dilute it to obtain a graphene oxide solution. Subsequently, slowly add 30% hydrogen peroxide solution to the solution to remove residual potassium permanganate. Add 400ml of deionized water, dilute the pH value of the mixed solution to pH=1, add appropriate amounts of 10% dilute hydrochloric acid and deionized water, and perform centrifugal mixing several times to make the pH value of the solution reach about 6~7, filter and vacuum dry at 60°C to obtain graphene oxide, i.e., the third powder. The graphene oxide was placed in a quartz crucible and thermally annealed in a tube furnace at 600° C. for 12 hours to obtain rGO, i.e., the fourth powder.

[0023] Put hard carbon powder, rGO, thiourea and urea in a mass ratio of 30:5:1:1 into the barrel of the high-temperature coating machine, close the discharge valve, turn on the cooling water switch, check the water supply, and connect the argon gas source. Start the agitator for pre-dispersion, set the main engine speed to 65-130 rpm, and the heating temperature is 5℃ / min. The temperature is raised to 550℃ at a rate of 5℃ / min, and the temperature is kept in a nitrogen atmosphere (flow rate = 120 ml / min) for 1 hour. In this process, thiourea is pyrolyzed into a sulfur source, and urea is pyrolyzed into a nitrogen source. Nitrogen and sulfur atoms are firmly doped into rGO through (C-N and C-S) bonds, which changes the morphology of rGO, increases the wrinkles to form a rough tray-like flake morphology of particle aggregation, and can effectively improve the electron and ion transmission pathways and improve the electrochemical performance. Then the heating temperature is set to 800°C at a rate of 5°C / min, and the mixing and heating are started, so that the rGO doped with sulfur atoms and nitrogen atoms is coated on the surface of the hard carbon powder to increase the electron transfer rate of the hard carbon. Then it is taken out and ground to obtain the co-doped hard carbon active material. The high-temperature coating machine can make the doping and coating processes proceed simultaneously, thereby saving production time and reducing costs. Example

[0024] Take walnut shell hard carbon material, wash, dry, crush and sieve it in sequence to obtain 450 mesh hard carbon particles, add the hard carbon particles into a ball mill, add trisodium phosphate powder, and ball mill to obtain a mixed powder, i.e., the first powder, add the mixed powder into a graphite sagger, transfer the graphite sagger to a tubular furnace, and keep it at 1100°C for 5.5 hours under a helium protective atmosphere. After cooling to room temperature with the furnace, take out the hard carbon powder, i.e., the second powder.

[0025] Take 3g of graphite powder and 2g of sodium nitrate, add them to concentrated sulfuric acid, put them in a magnetic stirrer and stir them continuously for 0.5 to 1h to obtain a mixed solution, take out the mixed solution for ice bath, and slowly add potassium permanganate powder to the mixed solution until the solution is dark brown, and control the temperature of the mixed solution below 20°C to prevent overheating and explosion. Continue stirring for 2h, keep the ice bath state during the period, and then add 100ml of deionized water to the solution to dilute it to obtain a graphene oxide solution. Subsequently, slowly add 30% hydrogen peroxide solution to the solution to remove residual potassium permanganate. Add 400ml of deionized water, dilute the pH value of the mixed solution to pH=1, add appropriate amounts of 10% dilute hydrochloric acid and deionized water, and perform centrifugal mixing several times to make the pH value of the solution reach about 6-7, filter and vacuum dry at 60°C to obtain graphene oxide, i.e., the third powder. The graphene oxide was placed in a quartz crucible and thermally annealed in a tube furnace at 700° C. for 12 hours to obtain rGO, i.e., the fourth powder.

[0026] Put hard carbon powder, rGO, thiourea and urea in a mass ratio of 30:4:1:1 into the barrel of the high-temperature coating machine, close the discharge valve, turn on the cooling water switch, check the water supply, and connect the argon gas source. Start the agitator for pre-dispersion, set the main engine speed to 75 rpm, and the heating temperature to 525°C at a rate of 5°C / min. Keep warm and ventilate in a helium atmosphere (flow rate = 120 ml / min) for 1.5 hours. In this process, nitrogen-sulfur co-doped rGO is obtained. Then set the heating temperature to 750°C at a rate of 5°C / min, treat for 1.5 hours, start mixing and heating, take out and grind to obtain a co-doped hard carbon active material. Example

[0027] A walnut shell hard carbon material is washed, dried, crushed and sieved in sequence to obtain hard carbon particles of 500 mesh, the hard carbon particles are added into a ball mill, disodium hydrogen phosphate powder is added, and a mixed powder is obtained by ball milling, i.e., the first powder, the mixed powder is added into a graphite sagger, the graphite sagger is transferred into a tubular furnace, and the mixture is kept at 1300° C. for 5 hours in a neon protective atmosphere, and after cooling to room temperature with the furnace, the hard carbon powder is taken out to obtain the second powder.

[0028] Take 3g of graphite powder and 2g of sodium nitrate, add them to concentrated sulfuric acid, put them in a magnetic stirrer and stir them continuously for 0.5 to 1h to obtain a mixed solution, take out the mixed solution for ice bath, and slowly add potassium permanganate powder to the mixed solution until the solution is dark brown, and control the temperature of the mixed solution below 20°C to prevent overheating and explosion. Continue stirring for 2h, keep the ice bath state during the period, and then add 100ml of deionized water to the solution to dilute it to obtain a graphene oxide solution. Subsequently, slowly add 30% hydrogen peroxide solution to the solution to remove residual potassium permanganate. Add 400ml of deionized water, dilute the pH value of the mixed solution to pH=1, add appropriate amounts of 10% dilute hydrochloric acid and deionized water, and perform centrifugal mixing several times to make the pH value of the solution reach about 6-7, filter and vacuum dry at 60°C to obtain graphene oxide, i.e., the third powder. The graphene oxide was placed in a quartz crucible and thermally annealed in a tube furnace at 800° C. for 12 hours to obtain rGO, i.e., the fourth powder.

[0029] Put hard carbon powder, rGO, thiourea and urea in a mass ratio of 30:3:1:1 into the barrel of the high-temperature coating machine, close the discharge valve, turn on the cooling water switch, check the water supply, and connect the argon gas source. Start the agitator for pre-dispersion, set the main engine speed to 85 rpm, and the heating temperature to 500°C at a rate of 5°C / min. Keep warm and ventilate in a neon atmosphere (flow rate = 120 ml / min) for 2 hours. In this process, nitrogen-sulfur co-doped rGO is obtained. Then set the heating temperature to 725°C at a rate of 5°C / min, treat for 2 hours, start the mixing and heating, take out and grind to obtain a co-doped hard carbon active material. Example

[0030] Take walnut shell hard carbon material, wash, dry, crush and sieve in sequence to obtain 550 mesh hard carbon particles, add the hard carbon particles into a ball mill, add sodium ammonium hydrogen phosphate powder, and ball mill to obtain a mixed powder, i.e., the first powder, add the mixed powder into a graphite sagger, transfer the graphite sagger to a tubular furnace, and keep it at 1400°C for 4.5 hours under an argon protective atmosphere. After cooling to room temperature with the furnace, take out the hard carbon powder, i.e., the second powder.

[0031] Take 3g of graphite powder and 2g of sodium nitrate, add them to concentrated sulfuric acid, put them in a magnetic stirrer and stir them continuously for 0.5 to 1h to obtain a mixed solution, take out the mixed solution for ice bath, and slowly add potassium permanganate powder to the mixed solution until the solution is dark brown, and control the temperature of the mixed solution below 20°C to prevent overheating and explosion. Continue stirring for 2h, keep the ice bath state during the period, and then add 100ml of deionized water to the solution to dilute it to obtain a graphene oxide solution. Subsequently, slowly add 30% hydrogen peroxide solution to the solution to remove residual potassium permanganate. Add 400ml of deionized water, dilute the pH value of the mixed solution to pH=1, add appropriate amounts of 10% dilute hydrochloric acid and deionized water, and perform centrifugal mixing several times to make the pH value of the solution reach about 6-7, filter and vacuum dry at 60°C to obtain graphene oxide, i.e., the third powder. The graphene oxide was placed in a quartz crucible and thermally annealed in a tube furnace at 1000 degrees Celsius for 12 hours to obtain rGO, i.e., the fourth powder.

[0032] Put hard carbon powder, rGO, thiourea and urea in a mass ratio of 30:2:1:1 into the barrel of the high-temperature coating machine, close the discharge valve, turn on the cooling water switch, check the water supply, and connect the argon gas source. Start the agitator for pre-dispersion, set the main engine speed to 115 rpm, and the heating temperature to 575°C at a rate of 5°C / min. Keep warm and ventilate in an argon atmosphere (flow rate = 120 ml / min) for 1 hour. In this process, nitrogen-sulfur co-doped rGO is obtained. Then set the heating temperature to 875°C at a rate of 5°C / min, treat for 2 hours, start the mixing and heating, take out and grind to obtain a co-doped hard carbon active material. Example

[0033] A walnut shell hard carbon material is washed, dried, crushed and sieved in sequence to obtain hard carbon particles of 600 mesh, the hard carbon particles are added into a ball mill, and sodium hydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate and sodium ammonium hydrogen phosphate powders are added, and the mixed powder, i.e., the first powder, is obtained by ball milling, the mixed powder is added into a graphite sagger, the graphite sagger is transferred into a tubular furnace, and the mixture is kept at 1500° C. for 4 hours under a krypton gas protective atmosphere, and after cooling to room temperature with the furnace, the hard carbon powder is taken out to obtain the second powder.

[0034] Take 3g of graphite powder and 2g of sodium nitrate, add them to concentrated sulfuric acid, put them in a magnetic stirrer and stir them continuously for 0.5 to 1h to obtain a mixed solution, take out the mixed solution for ice bath, and slowly add potassium permanganate powder to the mixed solution until the solution is dark brown, and control the temperature of the mixed solution below 20°C to prevent overheating and explosion. Continue stirring for 2h, keep the ice bath state during the period, and then add 100ml of deionized water to the solution to dilute it to obtain a graphene oxide solution. Subsequently, slowly add 30% hydrogen peroxide solution to the solution to remove residual potassium permanganate. Add 400ml of deionized water, dilute the mixed solution, add appropriate amounts of 10% dilute hydrochloric acid and deionized water, and centrifuge and mix several times to make the solution pH reach about 6-7, filter and vacuum dry at 60°C to obtain graphene oxide, i.e., the third powder. Put the graphene oxide into a quartz crucible and thermally anneal it in a 1200°C tube furnace for 12 hours to obtain rGO, i.e., the fourth powder.

[0035] Put hard carbon powder, rGO, thiourea and urea in a mass ratio of 30:1:1:1 into the barrel of the high-temperature coating machine, close the discharge valve, open the cooling water switch, check the water supply, and connect the argon gas source. Start the agitator for pre-dispersion, set the main engine speed to 130 rpm, and the heating temperature to 600°C at a rate of 5°C / min. Keep warm and ventilate in a krypton atmosphere (flow rate = 120 ml / min) for 1 hour. In this process, nitrogen-sulfur co-doped rGO is obtained. Then set the heating temperature to 950°C at a rate of 5°C / min, treat for 2 hours, start the mixing and heating, take out and grind to obtain a co-doped hard carbon active material. The co-doped hard carbon active material was tested, and the results are as follows Figures 2 to 4 shown.

[0036] The prepared co-doped hard carbon active material was mixed with carbon black conductive agent and binder (PVDF) in a mass ratio of 80:10:10, and N-methyl-2-pyrrolidone (NMP) was used as solvent. The above materials were stirred into a slurry and coated on aluminum foil, and then dried in a drying oven at 100°C for 12 hours to obtain a pole piece. The above-prepared pole piece was used as the experimental electrode, and metallic sodium was used as the counter electrode. The coated electrode was punched into a small round disc with a diameter of 12 mm and used as an active working electrode. The sulfonated PP membrane was used as a diaphragm, and 1 mol / L NaPF6 dissolved in ethylene carbonate (EC) and diethyl carbonate (DMC) was used as the electrolyte. The CR-2032 half-cell was assembled in an argon-filled glove box to test the electrochemical performance of the material. Using the LAND battery test system, the battery was activated at 0~2.5V, 0.05C, and then cycled at 0~2.5V, 1C, and 5C.

[0037] The obtained co-doped hard carbon active material was made into a working electrode according to the method provided by the present invention and the corresponding performance tests were carried out. The results are shown in Table 1.

[0038] Example <![CDATA[Initial reversible specific capacity / mAh g -1 > First coulombic efficiency% <![CDATA[100th reversible specific capacity / mAh g -1 > 100th Coulomb efficiency % <![CDATA[200th Reversible Specific Capacity / mAh g -1 > 200th Coulomb efficiency % <![CDATA[500th reversible specific capacity / mAh g -1 > 500th Coulomb efficiency % Example 1 271 98.8 247 98.6 249 98.2 245 97.5 Example 2 269 98.5 248 98.4 250 98.3 243 97.1 Example 3 273 98.6 245 98.4 253 98.2 247 96.9 Example 4 266 98.9 247 98.5 251 98.4 243 96.8 Example 5 270 98.7 246 98.5 247 98.3 240 96.7 Table 1 shows the cycle performance of the batteries in different embodiments, indicating that the co-doped hard carbon active material has good cycle stability and high initial efficiency for sodium ion batteries.

[0039] The embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0040] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.

[0041] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a co-doped hard carbon active material, characterized in that: include: S1: ball-milling the hard carbon particles and the phosphate to obtain a first powder; S2: keeping the first powder in a protective atmosphere at 1000° C. to 1500° C. for 4 to 6 hours to obtain a second powder; S3: adding graphite powder and sodium nitrate to a concentrated sulfuric acid solution, stirring for 0.5 to 1 hour, maintaining a solution temperature of 0° C. to 20° C., continuing to add potassium permanganate powder, and continuing to stir for 2 hours, then vacuum drying to obtain a third powder, and annealing the third powder at 600° C. to 1200° C. for 12 hours to obtain a fourth powder; S4: Keep the second powder, the fourth powder, thiourea and urea at 500°C to 600°C for 1 to 2 hours in a protective atmosphere with continuous stirring, then increase the temperature to 750°C to 950°C and keep it for 1 to 2 hours, take out and grind to obtain the co-doped hard carbon active material.

2. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: In the S4, the second powder, the fourth powder, the thiourea and the urea are put into the barrel of a high-temperature coating machine, the agitator speed is set to 75 to 130 revolutions per minute, the heating temperature is increased to 500 to 600°C at a rate of 5°C / min, and the temperature is kept warm for 1 to 2 hours under the protective atmosphere, and then the heating temperature is set to increase to 750 to 950°C at a rate of 5°C / min, and the temperature is kept warm for 1 to 2 hours. After taking out, grind to obtain the co-doped hard carbon active material.

3. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: In S3, the graphite powder and the sodium nitrate are added to the concentrated sulfuric acid solution together, and stirred for 0.5 hour to 1 hour, and the potassium permanganate powder is continuously added under ice bath condition, the solution temperature is maintained at 0°C to 20°C, and stirring is continued for 2 hours, 30% hydrogen peroxide solution is slowly dripped into the solution, and then 10% dilute hydrochloric acid and deionized water are added to make the pH value of the solution 6-7, and then vacuum drying is performed to obtain the third powder, and the third powder is annealed at 600°C to 1200°C for 12 hours to obtain the fourth powder.

4. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: The phosphate is at least one of sodium hydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate or sodium ammonium hydrogen phosphate.

5. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: The mass ratio of the graphite powder to the sodium nitrate is 3:

2.

6. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: The mass ratio of the second powder, the fourth powder, the thiourea and the urea is 30:5:1:

1.

7. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: The hard carbon particles are obtained by sequentially washing, drying, crushing and sieving walnut shell hard carbon materials, and the hard carbon particles are 400 meshes to 600 meshes.

8. The method for preparing a co-doped hard carbon active material according to claim 1, characterized in that: The protective atmosphere includes at least one component selected from nitrogen, helium, neon, argon or krypton.

9. The co-doped hard carbon active material obtained according to the preparation method according to any one of claims 1 to 8.

10. Use of the co-doped hard carbon active material according to claim 9 as an electrode material for sodium ion batteries.